1984
DOI: 10.1021/np50036a020
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents, 105. Zephyranthes grandiflora

Abstract: The history of certain Amaryllidaceous plants used in the primitive treatment of cancer can be traced to the fourth century B.C.2 In the genus Zephyranthes, Z. parulla Killip appears in a history of Peru (by Padre Cobo) dated 1653, for treating tumors, and Z. rosea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 2 publications
2
72
0
Order By: Relevance
“…1) As regards phytochemical studies on this plant, the isolation of phenanthridine alkaloids, fatty acids, sterols and triterpene alcohols have been previously reported. [2][3][4] Alkaloids isolated from the bulbs of the tribe Amaryllidaceae showed various pharmacological and microbiological effects, such as antiviral, 5) antimalarial, 6) cytotoxic [6][7][8][9] and antineoplastic activities, [10][11][12] as well as effects on diseases of the nervous system. 13) An EtOAc-soluble fraction of C. asiaticum var.…”
mentioning
confidence: 99%
“…1) As regards phytochemical studies on this plant, the isolation of phenanthridine alkaloids, fatty acids, sterols and triterpene alcohols have been previously reported. [2][3][4] Alkaloids isolated from the bulbs of the tribe Amaryllidaceae showed various pharmacological and microbiological effects, such as antiviral, 5) antimalarial, 6) cytotoxic [6][7][8][9] and antineoplastic activities, [10][11][12] as well as effects on diseases of the nervous system. 13) An EtOAc-soluble fraction of C. asiaticum var.…”
mentioning
confidence: 99%
“…In 1980s Pettit et al, and Ghosal et al, reported alkaloids, pancratistatin, (+)-epimaritidine, crinamine and haemanthamine, maritidine, ungeremine, criasbetaine, zefbetaine, zeflabetaine, alkaloidal phospholipids, two lactam alkaloid, three glucosyloxy alkaloid; flavans, 7-hydroxy-3',4'-methylenedioxyflavan and its glycoside, 7,4'-dihydroxy-3'-methoxyflavan and 7-methoxy-2'-hydroxy-4',5'-methylenedioxyflavan from bulbs and flowers of different species [28][29][30][31][32] 3-epimacronine, N-methylcrinasiadine, trisphaeridine, 5,6-dihydrolycorine, nigragillin, 2-hydroxy albomaculine, 6α-hydroxyhippeastidine, 10-deoxy-6α-hydroxyhippeastidine, 6β-hydroxyhippeastidine, 7-hydroxy-3',4'-methylenedioxyflavan 7-hydroxy-3',4'-methylenedioxyflavan and its glycoside, 7,4'-dihydroxy-3'-methoxyflavan and 7-methoxy-2'-hydroxy-4',5'-methylenedioxyflavan, maritidine, 2-O-glycerophosphoryllycorine, phosphatidyllycorines, phosphatidylpseudolycorines, phosphatidyllycoriniium methocation, 2-oxy phenanthridinium, zefbetaine, zeflabetaine, crinamine, haemanthamine, lycorine, pseudolycorine, narciclassine, protorimine, kalbreclassine, lycorine-1-O-β-D-glucoside, pseudolycorine-1-O-β-Dglucoside, criasbetaine, ungeremine [29,30] [39][40][41]. During this decade flavans, sterols were also reported from the same species [39].…”
Section: Traditional Usagementioning
confidence: 99%
“…In 1984 and 1990 Pettit et al, reported two antineoplastic compounds, pancratistatin from Z. grandiflora and trans-dihydronarciclasine from Z. candida bulbs using the P-388 lymphocytic leukemia bioassay [31,33].…”
Section: Antineoplastic Activitymentioning
confidence: 99%
“…The decoction of leaves of Z. candida has been used in South Africa as a remedy for diabetes mellitus and Z. parulla appears in the history of Peru as a treatment for tumors (Pettit et al, 1984). Z. rosea and Z. flava are used for a variety of therapeutic purposes in India (Ghosal et al, 1985;Ghosal et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, zefbetaine and zeflabetaine were isolated from Z. flava (Ghosal et al, 1986), and pretazettine and carinatine, along with lycorine, galanthine and haemanthanine from Z. carinata (Kobayashi et al, 1977). Previous phytochemical investigation of Z. grandiflora led to the isolation of pancratistatin (Pettit et al, 1984). GC/MS analysis of the bulb extracts of Z. concolor and Z. robusta showed the domination of galanthamine-type Amaryllidaceae alkaloids and these extracts possessed promising AChE inhibitory activity (Berkov et al, 2008;Cahlíková et al, 2010).…”
Section: Introductionmentioning
confidence: 99%